Mobile Notification for Mail Delivery for UUM Post Office - Hadad, Taha R. Mohamed M (2009)
The last two decades have witnessed rapid adoption and intense use of various information and communication technologies (ICTs) as an essential foundation for business activities. Presently, we are witnessing how the advent of the mobile and wireless technologies have influenced contemporary businesses and organisations. Mobile technologies such as mobile phones and personal digital assistants (PDAs) not only change the way people communicate, but also, change the way the postal service does business. Nowadays, postal offices are using new technology to improve the quality of their services. They introduce new services and products with the support of different information and communication technologies to reach millions of people all over the world. With mobile phones as a necessity to all people today, information could be sent faster to inform news regarding postal services including mail delivery services. Mail delivery service is an important service in post offices and the most needed especially for possibility of a post office using a mobile-based system to notify students about the status of postal delivery services. A requirement model was produced and a prototype was developed as part of the study.